Neurodynamic and Communication Analysis of Healthcare Teams during Simulation Debriefings. Issue 1 (June 2018) - Stevens, Ron; Willemsen-Dunlap, Ann; Gorman, Jamie; Galloway, Trysha; Grimm, David; Halpin, Donald
Objective: To determine whether a dynamical analysis of neural and communication data streams provide fine-grained insights into healthcare team debriefings. Background: Debriefing plays a key role in experiential learning activities such as healthcare simulation because it bolsters the transfer of experience into learning through a process of reflection. There have been few studies examining the neural and communication dynamics of teams as team members are supported by trained facilitators in making better sense of their performance. Method: Electroencephalographic (EEG)–derived brain waves and speech were recorded from experienced and medical student healthcare teams during post-simulation debriefings. Quantitative estimates of the neurodynamic organizations of individual team members and the team were modeled from the EEG data streams at different scalp locations and at frequencies from 1–40 Hz. In parallel the dynamics of speech turn taking were quantified by recurrence frequency analysis. Results: Neurodynamic organizations were preferentially detected from sensors over the parietal lobes with activities present in the alpha, beta and gamma frequency bands. Rhythmic structures emerged as correlations between speech, discussion blocks and team & team member neurodynamic organizations. Conclusion: Organizational representations help reveal the neurodynamic, communication, and cognitive structures of debriefing. Application: The quantitative neurodynamic and communication measures will allow direct comparisons of debriefing structures across teams and debriefing protocols.